The costs of rearing a buffalo calf from birth until weaning age at buffalo breeding and research centre, Telupid, Sabah - Ishak, Muhammad Hasifsafwan (2016)
Malaysia recently witnessed declining of its buffalo population at the rate of 1.2% per year which could be due to the lack of suitable land for extensive farming, lack of superior breeds, reproductive problems for example a low reproductive rate and poor calf rearing management. Calf rearing is important because it is the future replacement of the herd. Farmers may faces problem on maintaining farm sustainability probably because of they are not aware of rearing cost in the farm. Therefore, the objective of this study is to calculate the costs of rearing a buffalo calf from birth until weaning age. The calculation of costs were done in Microsoft Excel (Microsoft Corporation, Redmond, WA). A buffalo farm (Buffalo Breeding and Research Centre Farm) at Telupid Sabah was visited by a veterinary student in January, 2016 to gather inputs for this study. Inputs were collected by using a questionnaire (asked to farm manager) and by using farm records in 2015. The inputs gathered were farm general and health management and costs component such as healthcare costs, labor costs and treatment costs. The results of this study showed, on the extensive farm in 2015, there were 143 buffalo breeder and there were 133 buffalo calves born. The most common calf diseases in year 2015 were weight loss (15 cases), diarrhea (17 cases) and respiratory (3 cases).The age of weaning is three months. Calf management from birth until weaning was as followed; at birth, buffalo calf was identified with a tag and dewormed. The calf remained with their dam in the paddock until weaning and were given 0.5kg pellet per calf 3 weeks before weaning age. At weaning age, the calf was dewormed for second time. The calf was assumed not to eat grass before weaning age. The costs of rearing a calf only calculated the variable costs. The costs included feed costs (milk cost, pellet), id-tag, preventive treatment costs, labor costs (to feed calf). The cost of milk is calculated based on the current price of buffalo milk in the market (RM3.20). The cost of milk cost was calculated by taking the milk requirement per body weight for 90 consecutive days. This, taking account of the average daily gain of calf in the farm which is 0.6kg.Therefore, the costs of milk from birth until weaning is RM1,834.56. The costs of pellet, id tag and preventive treatment were RM1.14 per kg, RM2 per animal and RM0.50 per animal, respectively. The cost of rearing a buffalo calf from birth until weaning wasRM1842.46. The highest cost was the feed costs (99.85%), in which milk cost contributed 99.57% to overall cost of feed cost. Using costs of diarrhea, weight loss and respiratory RM30.16, RM30.16 and RM1.46 per animal respectively, the total costs of treating the sick calves were RM969.44 per herd per year. This means, the costs of rearing buffalo calves were RM246,016.77per herd per year, where treatment costs is 0.39% of the total rearing costs per herd per year. This study revealed that the cost of rearing a calf is expensive due to milk cost that is the contributed to majorcontributor to the overall cost. The disease treatment only contributed 0.39% to the total cost of rearing per herd peryear,however, the high prevalence of diseases could cause the farm to have high treatment costs. Hence, farmer needs to improve the herd health to reduce the overall total cost of rearing. The cost from milk cost can be reduce by reduce the age of weaning. However further research need to be done in future for the acceptable weaning age in the farm.